From status inconsistency to revisionism: A study of Russian foreign policy from 1991 to the colour revolutions / Esmaeil Mazloomi - Esmaeil , Mazloomi (2020)
This study is an analysis of Russian Federation’s grand strategic orientations and its foreign policy behaviours between two major shocks; the disintegration of the Union of the Soviet Socialist Republics (USSR), and the colour revolutions in newly independent contries that were parts of USSR. While the collapse of Soviet Union and the end of cold war in 1991 fostered an optimistic view of Russia’s collaboration within the Western liberal order. The wave of “Rose”, “Orange” and “Tulip” revolutions in Georgia, Ukraine and Kirgyzstan (2003-2005) cause Russia to adopt a radical revisionism towards the statu quo order. This study attempts to present the rationale behind such “paradigm change” in Russia’s grand strategic orientations between two major shocks, from the search for the status via different enhancement strategies in light of status quo from, to revisionism after the colour revolutions. It aims to explain why Russia’s grand strategy changed to revisionism – anti status quo - after a phase of committing to reassurance of the Western liberal order, and how Russia become discounted with the “constitutive and normative structure” of international order. Meanwhile, this study uses the post-Soviet Russia as a case with which to demonstrate the influence of status concern, inconsistency/dilemma based on a qualitative method. In order to explain why and how Russia’s grand strategic orientation has been created and changed, this study employs content analysis. The sources available to conduct the research came from a collection of archival official documents, speeches and transcripts of leading figures of Russia involved in the state’s grand strategy making process and foreign policy actions, from 1992 to 2008. Using existing explanations, this study develops an alternative theoretical rational on why a rising power may adopt revisionism. It argues revisionism is rather partially outcome of concern over a state’s status, in particular the status recognition dilemma resulting from the failure of status seeking process. Revisionism in this account is an outcome of the status enhancement process of changing perceptions from status inconsistency to status dilemma – achievable to unachievable status. On this alternative account, Russia’s revisionism was rather partially due to internal effects of the perceived status dilemma. It was in a part a response to the lack of status recognition from the West; in particular, the process of changing perceptions from status inconsistency to recognition dilemma caused Russian leaders to adopt revisionism, particularly after the colour revolutions. The findings of this study provide confirmatory evidence that the concern over Russia’s and the desire to have an equal role in the order shaped in post-Cold war era, remains consistently in the post-Soviet Russian grand strategic thinking and orientations. While the perception of status inconsistency led Russia to adopt enhancement strategies through reassuring the West and within the framework of liberal order up to the mid-2000s. However, the failure of the strategies to enhance its status or correct the inconsistency, due to lack of recognition from the West, left Russia with no choice but seek a revision of the post-Cold war liberal order fundamentally, in particular after the colour revolutions.